LY3298176, a novel dual GIP and GLP-1 receptor agonist for the treatment of type 2 diabetes mellitus: From discovery to clinical proof of concept - Coskun, Tamer; Sloop, Kyle W.; Loghin, Corina; Alsina-Fernandez, Jorge; Urva, Shweta; Bokvist, Krister B.; Cui, Xuewei; Briere, Daniel A.; Cabrera, Over; Roell, William C.; Kuchibhotla, Uma; Moyers, Julie S.; et al. (Molecular metabolism (Germany), 2018)
A novel dual GIP and GLP-1 receptor agonist, LY3298176, was developed to determine whether the metabolic action of GIP adds to the established clinical benefits of selective GLP-1 receptor agonists in type 2 diabetes mellitus (T2DM). LY3298176 is a fatty acid modified peptide with dual GIP and GLP-1 receptor agonist activity designed for once-weekly subcutaneous administration. LY3298176 was characterised in vitro, using signaling and functional assays in cell lines expressing recombinant or endogenous incretin receptors, and in vivo using body weight, food intake, insulin secretion and glycemic profiles in mice. A Phase 1, randomised, placebo-controlled, double-blind study was comprised of three parts: a single-ascending dose (SAD; doses 0.25–8 mg) and 4-week multiple-ascending dose (MAD; doses 0.5–10 mg) studies in healthy subjects (HS), followed by a 4-week multiple-dose Phase 1 b proof-of-concept (POC; doses 0.5–15 mg) in patients with T2DM (ClinicalTrials.gov no. NCT02759107). Doses higher than 5 mg were attained by titration, dulaglutide (DU) was used as a positive control. The primary objective was to investigate safety and tolerability of LY3298176. LY3298176 activated both GIP and GLP-1 receptor signaling in vitro and showed glucose-dependent insulin secretion and improved glucose tolerance by acting on both GIP and GLP-1 receptors in mice. With chronic administration to mice, LY3298176 potently decreased body weight and food intake; these effects were significantly greater than the effects of a GLP-1 receptor agonist. A total of 142 human subjects received at least 1 dose of LY3298176, dulaglutide, or placebo. The PK profile of LY3298176 was investigated over a wide dose range (0.25–15 mg) and supports once-weekly administration. In the Phase 1 b trial of diabetic subjects, LY3298176 doses of 10 mg and 15 mg significantly reduced fasting serum glucose compared to placebo (least square mean [LSM] difference [95% CI]: −49.12 mg/dL [−78.14, −20.12] and −43.15 mg/dL [−73.06, −13.21], respectively). Reductions in body weight were significantly greater with the LY3298176 1.5 mg, 4.5 mg and 10 mg doses versus placebo in MAD HS (LSM difference [95% CI]: −1.75 kg [−3.38, −0.12], −5.09 kg [−6.72, −3.46] and −4.61 kg [−6.21, −3.01], respectively) and doses of 10 mg and 15 mg had a relevant effect in T2DM patients (LSM difference [95% CI]: −2.62 kg [−3.79, −1.45] and −2.07 kg [−3.25, −0.88], respectively. The most frequent side effects reported with LY3298176 were gastrointestinal (vomiting, nausea, decreased appetite, diarrhoea, and abdominal distension) in both HS and patients with T2DM; all were dose-dependent and considered mild to moderate in severity. Based on these results, the pharmacology of LY3298176 translates from preclinical to clinical studies. LY3298176 has the potential to deliver clinically meaningful improvement in glycaemic control and body weight. The data warrant further clinical evaluation of LY3298176 for the treatment of T2DM and potentially obesity. •LY3298176 activates both GIP and GLP-1 receptor signaling in vitro.•LY3298176 lowers blood glucose in mice through actions on both incretin receptors.•LY3298176 reduced fasting glucose in humans with type 2 diabetes.•Weight loss was greater with LY3298176 than the selective GLP-1 receptor agonist, dulaglutide in healthy humans.•Tolerability of LY3298176 was comparable to GLP-1 receptor agonists.